Spectrum of Abnormal Cervical Cytology in Papanicolaou (PAP) Smears - Ghazala Mudassir, Mariam Abid, Hania Naveed (Journal of Rawalpindi Medical College, 2018)
Background: To determine the frequency of abnormal cytological findings in pap smears of women in a local population in Pakistan. Methods: In this observational study conventional PAP smear was collected, from squamocolumnar junction, using an Ayer’s spatula in clockwise direction for 3600 after exposing the cervix by a Cusco speculum. The endocervical smears were made by rotating the endocervical brush. The samples collected were transferred to glass slide and then slides were fixed in 95% ethyl alcohol. The slides were then sent to pathology laboratory for histopathological examination . The adequacy and reporting of pap smears was based on 2001 Bethesda system. Results: Majority of the patients in the reproductive age group (18- 38 years). Most of the patients (49.6%) had no cervical complaint and they underwent the procedure for screening. In symptomatic patients common presenting complaints were cervicitis (17.1%) and vaginal discharge (11.3%).Out of the total 1984 pap smears, 99.1% were negative for intraepithelial lesion or malignancy. The precursor neoplastic lesions were observed in 0.8%, which included Atypical Squamous Cells of Uncertain Significance (ASCUS) (0.6%), Atypical Glandular Cells of Uncertain Significance (AGUS) (0.2%) and High Grade Squamous Intraepithelial Lesion (HSIL)(0.1%). ASCUS was seen mostly in young age group that is 18- 38 years while HSIL and AGC were identified in patients more than 50 years of age. Non-specific inflammatory pattern was seen in 17.6%. Atrophic pattern was observed in 2.5% smears. Conclusion- A significant number of abnormal pap smears were negative for intraepithelial lesion or malignancy.Epithelial cell abnormalities, though less prevalent were also seen.